PELAYANAN PENYEBARAN INJIL BERDASARKAN 2 KORINTUS 6:1-10 - David Susilo Pranoto (Sekolah Tinggi Teologi Arastamar Bengkulu, 2016)
This 2nd Corinthian letter, written by the Apostle Paul, was addressed to the Corinthians. This letter is intended for the purpose, so that in conveying the gospel has the correct method so that the gospel can be accepted. The duty of believers is to convey the gospel / good news to everyone who does not know Christ. In writing this article we will explore how the Apostle Paul's perspective on the ministry of spreading the gospel based on 2 Corinthians 6: 1-10. Therefore through this writing, we will again remind and refresh believers about the importance of the ministry of spreading the gospel.